DNA methylation of amino acid transporter genes in the human placenta. (December 2017) - Simner, C.; Novakovic, B.; Lillycrop, K.A.; Bell, C.G.; Harvey, N.C.; Cooper, C.; Saffery, R.; Lewis, R.M.; Cleal, J.K.
Abstract: Introduction: Placental transfer of amino acids via amino acid transporters is essential for fetal growth. Little is known about the epigenetic regulation of amino acid transporters in placenta. This study investigates the DNA methylation status of amino acid transporters and their expression across gestation in human placenta. Methods: BeWo cells were treated with 5-aza-2′-deoxycytidine to inhibit methylation and assess the effects on amino acid transporter gene expression. The DNA methylation levels of amino acid transporter genes in human placenta were determined across gestation using DNA methylation array data. Placental amino acid transporter gene expression across gestation was also analysed using data from publically available Gene Expression Omnibus data sets. The expression levels of these transporters at term were established using RNA sequencing data. Results: Inhibition of DNA methylation in BeWo cells demonstrated that expression of specific amino acid transporters can be inversely associated with DNA methylation. Amino acid transporters expressed in term placenta generally showed low levels of promoter DNA methylation. Transporters with little or no expression in term placenta tended to be more highly methylated at gene promoter regions. The transporter genes SLC1A2, SLC1A3, SLC1A4, SLC7A5, SLC7A11 and SLC7A10 had significant changes in enhancer DNA methylation across gestation, as well as gene expression changes across gestation. Conclusion: This study implicates DNA methylation in the regulation of amino acid transporter gene expression. However, in human placenta, DNA methylation of these genes remains low across gestation and does not always play an obvious role in regulating gene expression, despite clear evidence for differential expression as gestation proceeds. Highlights: This study implicates DNA methylation in the regulation of amino acid transporter gene expression. In trophoblast-like cells, inhibition of DNA methylation altered the expression of specific amino acid transporters. Promoter DNA methylation of human placental amino acid transporter genes remains low across gestation. Specific amino acid transporter genes showed changes in both enhancer region methylation and expression across gestation.